2021
DOI: 10.3389/fnut.2021.743909
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Extraction, Characterization, and Applications of Bioactive Peptides From Pressed Black Cumin Seed Cake

Abstract: Plenty of black cumin cake was generated as a natural waste material after pressing the oil. Nigella sativa (black cumin) seeds and cakes are of precious nutritional value as they contain proteins, phenolics, essential amino acids, and bioactive compounds. Owing to their antioxidant properties, scientists and food manufacturers have extensively developed them. Notably, global awareness among consumers about the benefits of innovative food ingredients has been increased. Meanwhile, it has to be noted that vast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Ultrafiltration, RP-HPLC, size exclusion chromatography, and ion-exchange chromatography, can all be used to purify bioactive peptides. Additionally, for protein identification, analytical techniques such as mass spectrometry (MS), electrospray ionization MS, matrix-assisted laser desorption ionization time-of-flight MS, liquid chromatography-MS/MS, and hydrophilic interaction liquid chromatography (HILIC) are widely utilized ( 109 ).…”
Section: The Sources Of Bioactive Peptidesmentioning
confidence: 99%
“…Ultrafiltration, RP-HPLC, size exclusion chromatography, and ion-exchange chromatography, can all be used to purify bioactive peptides. Additionally, for protein identification, analytical techniques such as mass spectrometry (MS), electrospray ionization MS, matrix-assisted laser desorption ionization time-of-flight MS, liquid chromatography-MS/MS, and hydrophilic interaction liquid chromatography (HILIC) are widely utilized ( 109 ).…”
Section: The Sources Of Bioactive Peptidesmentioning
confidence: 99%
“…Results generated from the experimental data showed that the protein content varied from 14.92 to 21.21 g soluble protein/100 g defatted seed flour. A recent study also reveals the Nigella sativa seed cake to be a valuable source of protein with 37.40% protein constituents (Zaky et al, 2021). A similar analysis of defatted M. oleifera seed showed a protein content varying from 32% to 62.8% (Saa et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, black cumin seeds have been an excellent source of nutritional compounds such as minerals, vitamins, and dietary fibers (Kooti et al, 2016). Previous studies have evaluated the chemical composition of black cumin seeds and found that the seeds contain a good amount of fat (38.20%), carbohydrate (31.94%), crude fiber (7.95%), and protein (20.85%) (Zaky et al, 2021). In addition, fractionation studies of N. sativa seed protein showed that it contains numerous protein bands ranging from 10 to 94 kDa molecular mass (Molla et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Black cumin seeds contain, on average, 34% of fat, 22% of protein, 32% of carbohydrates, 8% of fiber, especially the insoluble fraction, and 4% of ash [ 2 ]. In the analysis of the chemical composition of black cumin seeds, it is worth paying attention to the high protein quality with different biological activities and qualitative composition of fat, 20% of which are unsaturated fatty acids, including linoleic and oleic acids [ 3 ].…”
Section: Introductionmentioning
confidence: 99%